Pengaruh Profitabilitas dan Kebijakan Deviden Terhadap Return Saham Melalui Nilai Perusahaan - Yulianti Adam; Ariawan Ariawan; Musafir Musafir (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze and explain the influence of profitability and dividend policy on stock returns through firm value as an intervening variable. A quantitative approach was employed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The sample consisted of 20 companies selected through purposive sampling based on specific criteria. The results reveal that profitability does not have a significant effect on firm value, while dividend yield significantly influences firm value. Firm value has a significant impact on stock returns. Profitability and dividend policy each have a direct and significant effect on stock returns. However, the indirect effect of profitability on stock returns through firm value is not significant. In contrast, dividend policy significantly affects stock returns through firm value. These findings indicate that while profitability is important for investors, firm value does not serve as a strong mediating factor in this relationship. On the other hand, dividend policy enhances the perceived value of the firm and indirectly contributes to increased stock returns. The implications of this study provide insights for corporate management to consider microeconomic factors, such as dividend policy, which play a critical role in shaping firm value and attracting investors through improved stock return performance.